Informology. It’s relationship and interaction with documentation science and informatics - Voverienė, Ona (Information & Media, 1995)
In the article is given a short review of development of information science since the end of the 19th century till now. On the first stage of development - the theory of information science was created by Paul Otlet and Henry Lafontaine as Documentation science. In the period of scientific-technical revolution information science has got new life and new paradigm. In the USSR it was developing as informatics scientific discipline, and in the West as Information Science. In it’s frame two main trends had formed: one of them was oriented to researches of social phenomenon of information science, the other - on the machinery forms and methods of transformation and transmission of information. From this moment had begun the revolutionary development of information science in the result of which new paradigm - informology has appeared. Informology - it is a new scientific discipline of information science, which investigates the nature, structure and characteristics of information and it’s resources in order to create new optimal ways and methods of their managing and using.